Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Compute the Fourier series for $x^3$ and use it to compute the value of $\sum\limits_{n = 1}^{\infty} \frac{1}{n^4}$.

I determined the coefficients of the Fourier series, which are

$$a_0 = \dfrac{\pi^3}{2}; \qquad a_n = \dfrac{6(\pi^2 n^2 - 2)(-1)^n + 12}{\pi n^4}$$

Then, I get

$$x^3 = \dfrac{\pi^3}{4} + \sum\limits_{n = 1}^{\infty} \dfrac{6(\pi^2 n^2 - 2)(-1)^n + 12}{\pi n^4}\cos(nx)$$

If $x = \pi$, then

$$\begin{aligned} \pi^3 &= \dfrac{\pi^3}{4} + \sum\limits_{n = 1}^{\infty} \dfrac{6(\pi^2 n^2 - 2)(-1)^n + 12}{\pi n^4}\cos(n\pi)\\ \dfrac{3\pi^3}{4} &= \sum\limits_{n = 1}^{\infty} \dfrac{6(\pi^2 n^2 - 2)(-1)^n + 12}{\pi n^4}(-1)^n \end{aligned}$$

I'm stuck. It's easy to compute $\sum\limits_{n = 1}^{\infty} \frac{1}{n^2}$, using the Fourier series, but for this type of problem I'm stuck.

Any comments or suggestions? By the way, I know that

$$\sum\limits_{n = 1}^{\infty} \dfrac{1}{n^4} = \dfrac{\pi^4}{90}$$

I need to know how to get there.

share|improve this question
add comment

2 Answers 2

up vote 6 down vote accepted

From your identity

\begin{equation*} \frac{3\pi ^{3}}{4}=\sum_{n=1}^{\infty }\frac{6(\pi ^{2}n^{2}-2)(-1)^{n}+12}{ \pi n^{4}}(-1)^{n} \end{equation*}

expanding the right hand side and using the result $\sum_{n=1}^{\infty }\frac{1}{n^{2}}=\frac{\pi^2}{6}$, we get

\begin{eqnarray*} \frac{3\pi ^{4}}{4} &=&\sum_{n=1}^{\infty }\frac{6(\pi ^{2}n^{2}-2)(-1)^{n}+12}{n^{4}}(-1)^{n} \\ &=&6\pi ^{2}\sum_{n=1}^{\infty }\frac{1}{n^{2}}-12\sum_{n=1}^{\infty }\frac{1 }{n^{4}}+12\sum_{n=1}^{\infty }\frac{(-1)^{n}}{n^{4}} \\ &=&\pi ^{4}-12\sum_{n=1}^{\infty }\frac{1}{n^{4}}-12\sum_{n=1}^{\infty } \frac{(-1)^{n-1}}{n^{4}}. \end{eqnarray*}

Now we need to express the alternating series $\sum_{n=1}^{\infty }\frac{ (-1)^{n-1}}{n^{4}}$ in terms of $\sum_{n=1}^{\infty }\frac{1}{n^{4}}$, e.g. as follows

\begin{eqnarray*} \sum_{n=1}^{\infty }\frac{\left( -1\right) ^{n-1}}{n^{4}} &=&\sum_{n=1}^{ \infty }\frac{1}{n^{4}}-2\sum_{n=1}^{\infty }\frac{1}{(2n)^{4}} =\sum_{n=1}^{\infty }\frac{1}{n^{4}}-\frac{1}{2^{3}}\sum_{n=1}^{\infty } \frac{1}{n^{4}}=\frac{7}{8}\sum_{n=1}^{\infty }\frac{1}{n^{4}}. \end{eqnarray*}

Then

\begin{eqnarray*} \frac{3\pi ^{4}}{4} &=&\pi ^{4}-12\sum_{n=1}^{\infty }\frac{1}{n^{4}}-\frac{ 21}{2}\sum_{n=1}^{\infty }\frac{1}{n^{4}} \\ &=&\pi ^{4}-\frac{45}{2}\sum_{n=1}^{\infty }\frac{1}{n^{4}}. \end{eqnarray*}

Solving for $\sum_{n=1}^{\infty }\frac{1}{n^{4}}$ we finally obtain

\begin{equation*} \sum_{n=1}^{\infty }\frac{1}{n^{4}}=\frac{2}{45}\left( \pi ^{4}-\frac{3\pi ^{4}}{4}\right) =\frac{\pi ^{4}}{90}. \end{equation*}

share|improve this answer
    
What a pure genius. I haven't seen that type of derivation of the alternating series before. Nice one. It will be useful for my computation! :D –  NasuSama Feb 23 at 23:35
    
Many thanks. Glad to help. Google Dirichlet eta function or Alternating zeta function. –  Américo Tavares Feb 23 at 23:41
add comment

$\newcommand{\+}{^{\dagger}}% \newcommand{\angles}[1]{\left\langle #1 \right\rangle}% \newcommand{\braces}[1]{\left\lbrace #1 \right\rbrace}% \newcommand{\bracks}[1]{\left\lbrack #1 \right\rbrack}% \newcommand{\ceil}[1]{\,\left\lceil #1 \right\rceil\,}% \newcommand{\dd}{{\rm d}}% \newcommand{\down}{\downarrow}% \newcommand{\ds}[1]{\displaystyle{#1}}% \newcommand{\equalby}[1]{{#1 \atop {= \atop \vphantom{\huge A}}}}% \newcommand{\expo}[1]{\,{\rm e}^{#1}\,}% \newcommand{\fermi}{\,{\rm f}}% \newcommand{\floor}[1]{\,\left\lfloor #1 \right\rfloor\,}% \newcommand{\half}{{1 \over 2}}% \newcommand{\ic}{{\rm i}}% \newcommand{\iff}{\Longleftrightarrow} \newcommand{\imp}{\Longrightarrow}% \newcommand{\isdiv}{\,\left.\right\vert\,}% \newcommand{\ket}[1]{\left\vert #1\right\rangle}% \newcommand{\ol}[1]{\overline{#1}}% \newcommand{\pars}[1]{\left( #1 \right)}% \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\pp}{{\cal P}}% \newcommand{\root}[2][]{\,\sqrt[#1]{\,#2\,}\,}% \newcommand{\sech}{\,{\rm sech}}% \newcommand{\sgn}{\,{\rm sgn}}% \newcommand{\totald}[3][]{\frac{{\rm d}^{#1} #2}{{\rm d} #3^{#1}}} \newcommand{\ul}[1]{\underline{#1}}% \newcommand{\verts}[1]{\left\vert\, #1 \,\right\vert}$ \begin{align} \pi x\cot\pars{\pi x}&=1 + \sum_{n = 1}^{\infty}{2x^{2} \over x^{2} - n^{2}} =1 - 2x^{2}\sum_{n = 1}^{\infty}{1 \over n^{2}} - 2x^{4}\sum_{n = 1}^{\infty}{1 \over n^{4}} - 2x^{6}\sum_{n = 1}^{\infty}{1 \over n^{6}} - \cdots \end{align}

$$ \pi x^{1/2}\cot\pars{\pi x^{1/2}}=1 - 2x\sum_{n = 1}^{\infty}{1 \over n^{2}} - 2x^{2}\sum_{n = 1}^{\infty}{1 \over n^{4}} - 2x^{3}\sum_{n = 1}^{\infty}{1 \over n^{6}} - \cdots $$ For $\verts{z} \sim 0$: \begin{align} z\cot\pars{z}&={z \over \tan\pars{z}} \sim {z \over z + z^{3}/3 + 2z^{5}/15} ={1 \over 1 + z^{2}/3 + 2z^{4}/15} \\[3mm]&\sim 1 - \pars{{z^{2} \over 3} + {2z^{4} \over 15}} + \pars{{z^{2} \over 3} + {2z^{4} \over 15}}^{2} \sim 1 - {z^{2} \over 3} - {2z^{4} \over 15} + {z^{4} \over 9} =1 - {z^{2} \over 3} - {z^{4} \over 45} \end{align}

$$ \pi x^{1/2}\cot\pars{\pi x^{1/2}}\sim 1 - {\pi^{2} \over 3}\,x - {\pi^{4} \over 45}\,x^{2} $$

$$ \color{#00f}{\large\sum_{n = 1}^{\infty}{1 \over n^{4}}} = -\,\half\,\pars{-\,{\pi^{4} \over 45}} = \color{#00f}{\large{\pi^{4} \over 90}} $$

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.